Hydrogen and Methane‐Based Breath Testing in Gastrointestinal Disorders: The North American Consensus. (May 2017) - Rezaie, Ali; Buresi, Michelle; Lembo, Anthony; Lin, Henry; McCallum, Richard; Rao, Satish; Schmulson, Max; Valdovinos, Miguel; Zakko, Salam; Pimentel, Mark
Abstract : Objectives: Breath tests (BTs) are important for the diagnosis of carbohydrate maldigestion syndromes and small intestinal bacterial overgrowth (SIBO). However, standardization is lacking regarding indications for testing, test methodology and interpretation of results. A consensus meeting of experts was convened to develop guidelines for clinicians and research. Methods: Pre‐meeting survey questions encompassing five domains; indications, preparation, performance, interpretation of results, and knowledge gaps, were sent to 17 clinician‐scientists, and 10 attended a live meeting. Using an evidence‐based approach, 28 statements were finalized and voted on anonymously by a working group of specialists. Results: Consensus was reached on 26 statements encompassing all five domains. Consensus doses for lactulose, glucose, fructose and lactose BT were 10, 75, 25 and 25 g, respectively. Glucose and lactulose BTs remain the least invasive alternatives to diagnose SIBO. BT is useful in the diagnosis of carbohydrate maldigestion, methane‐associated constipation, and evaluation of bloating/gas but not in the assessment of oro‐cecal transit. A rise in hydrogen of ≥20 p.p.m. by 90 min during glucose or lactulose BT for SIBO was considered positive. Methane levels ≥10 p.p.m. was considered methane‐positive. SIBO should be excluded prior to BT for carbohydrate malabsorption to avoid false positives. A rise in hydrogen of ≥20 p.p.m. from baseline during BT was considered positive for maldigestion. Conclusions: BT is a useful, inexpensive, simple and safe diagnostic test in the evaluation of common gastroenterology problems. These consensus statements should help to standardize the indications, preparation, performance and interpretation of BT in clinical practice and research.